The influence of stress hyperglycemia on consciousness disturbance and short- and long-term outcomes in stroke patients without documented diabetes: Differences between ischemic and hemorrhagic stroke - Jing Feng; Chang He; Hongbo San; Mengsi Zhan; Hongyu Zhang; Jianheng Gu; Hongqian Fu; Jiahao Yao; Lang Li; Xuefeng Wang (PLoS ONE, 2025)
Background Although hyperglycemia is a well-known prognostic factor in diabetic stroke patients, its impact on outcomes in individuals without documented diabetes remains insufficiently explored. This study aimed to investigate the relationship between stress-induced hyperglycemia and both short- and long-term mortality, as well as impaired consciousness, in patients without documented diabetes with ischemic or hemorrhagic stroke. Methods A retrospective cohort study was conducted using the MIMIC-IV (v3.1) database, including ICU-admitted patients without documented diabetes (ischemic or hemorrhagic stroke identified via ICD-9/10 codes). Exclusion criteria were: age < 18 years, missing glucose values, and severe impairment of consciousness upon ICU admission, defined as a Glasgow Coma Scale (GCS) score < 8. After applying these criteria, 4,151 patients were enrolled. Propensity score matching (PSM) was performed to balance baseline covariates between the hyperglycemic (HG) and non-hyperglycemic (Non-HG) groups. Cox proportional hazards models and Kaplan-Meier survival curves were used to assess the impact of hyperglycemia on mortality and neurological outcomes. Then subgroup analysis was conducted. Results Following PSM, 1,170 matched pairs were analyzed. In patients with hemorrhagic stroke (HS), stress hyperglycemia was associated with an increased 1-year mortality risk (HR = 0.71, p = 0.029). Among ischemic stroke (IS) patients, hyperglycemia independently predicted both in-hospital and 1-year mortality (HR range: 0.65–0.79, p < 0.001). Kaplan-Meier analyses showed significantly poorer survival in hyperglycemic patients. Subgroup analysis demonstrated that stress hyperglycemia was particularly detrimental in HS patients with heart failure, pneumonia, vasopressin use, or severe neurological impairment (GCS < 8 with heart failure). In IS patients, hyperglycemia was significantly associated with worse outcomes in those with advanced age, coronary artery disease, COPD, pneumonia, renal failure, or norepinephrine treatment. Conclusion Stress hyperglycemia independently predicts poor outcomes in stroke without documented diabetes, especially in ischemic subtypes. These findings highlight the importance of early glycemic assessment and tailored management strategies. Further research is warranted to validate causal mechanisms. In hemorrhagic stroke, its impact appears more delayed, affecting long-term prognosis. These findings support the need for early recognition and tailored glycemic control strategies based on stroke subtype.